Manajemen Pendidikan Vokasi Dalam Membentuk Pembelajaran Link and Match Dengan Dunia Industri - Sugiyantoro, Sugiyantoro; Irham, Irham (CV. ULIL ALBAB CORP, 2025)
Vocational education management in delivering Indonesian human resources, especially the younger generation, to be able to appear as actors of development, and take part in the international arena. Vocational education has a crucial role in producing human resources (HR) who are ready to face the challenges and opportunities of Industry 4.0. However, there is still a significant gap between the output of vocational education and the real needs of the industrial world, often referred to as the